LANGUAGE DEVELOPMENT DESIGN BASED ON ANALYSIS OF SUNDANESE LANGUAGE INTERFERENCE IN INDONESIAN LANGUAGE LEARNING - Hanifah, Ifah; Indra Dewi, Figiati; Arifah, Dini; Anjsmara, Aan (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2025)
This research is motivated by the large number of students who use the Sundanese language in the Indonesian language learning process. Learning is a formal process that requires students to use a wide variety of Indonesian languages. Based on this, it is necessary to design a framework for Indonesian language development so that the use of the language in learning follows established rules. This is important to study so that the Indonesian learning process, especially the process of fostering the leading Indonesian language, can create students who have a positive attitude and awareness of language. A considerable amount of intervention research has been conducted, but what distinguishes this research from previous studies is its discussion of the design of Indonesian language development. The research method employed is a qualitative descriptive approach, utilizing observation, interviews, and documentation techniques. The results of the analysis showed the dominance of morphological interference in the form of the use of prefixes, suffixes, and typical Sundanese confixes such as ”nge-, ”-keun”, and ”ka-an” in the Indonesian of students. These forms deviate from the standard Indonesian rules and impact the quality of language use in the formal learning process. Based on these findings, a draft coaching strategy was prepared, which included the introduction of the assisted community, goal setting, material determination, application of smart competition as a coaching method, and continuous evaluation. This draft is intended to serve as a reference for the development of contextual Indonesian language coaching, aiming to reduce interference and enhance students' language skills.